The formal properties of non paradigmatic ’se’ - Romero, Juan Romero; Ormazabal, Javier (Borealis – An International Journal of Hispanic Linguistics, 2019)
Following Oca (1914), this article argues that passive and impersonal se constructions in Spanish are regular transitive constructions where the pronominal clitic seis the argumental subject. Several arguments (secondary predication, non-argumental predicates, control and obviation, anaphora binding, active morphology or its alignment with overt nominative pronouns, among others)show that (i)bothconstructions are active structures, (ii)despite what agreement facts might suggest, in both the internal argument of the verb is not the subject but the direct object throughout the derivation, (iii) se is the active nominative pronominal subject of the construction. We argue that the alleged ‘special’ properties of passive-se are not construction-specific but follow from the lexical specifications of se agreeing with Tense as a quirky subject.